Effect of Pregnancy on Sebum Excretion. Issue 5712 (27th June 1970) - Burton, J. L.; Cunliffe, W. J.; Millar, D. G.; Shuster, Sam
Abstract : Sebum excretion rates from forehead skin were measured serially during and after pregnancy in 10 normal women. Only minor fluctuations occurred during the middle and last trimesters of pregnancy, but there was a pronounced decrease in the postpartum period. Probably a powerful sebotrophic factor is present in pregnancy, but its nature is conjectural.